2020
DOI: 10.1111/jcal.12517
|View full text |Cite
|
Sign up to set email alerts
|

To simplify or not? Facilitating English L2 users' comprehension and processing of open educational resources in English using text simplification

Abstract: Open Educational Resources (OER) aim to provide equal access to education. Yet, as the language level used in OER presents a barrier to many learners, there is a need to make these resources more comprehensible. This study combined eye‐tracking methodology and comprehension assessment to explore the effect of text simplification on English second language (L2) users, while also accounting for text organizational structure and individual predispositions. A total of 37 adult English L2 users took part in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…A common approach among CALL is to simplify a text so as to make it more accessible for the L2 learner [108]. Morris, et al, 2013 [156].…”
Section: Improving Readabilitymentioning
confidence: 99%
“…A common approach among CALL is to simplify a text so as to make it more accessible for the L2 learner [108]. Morris, et al, 2013 [156].…”
Section: Improving Readabilitymentioning
confidence: 99%
“…Text Frontiers in Psychology frontiersin.org simplification, in natural language processing, aims at producing a simplified version of the original sentence to facilitate reading and understanding. Studies showed that the simplified text could benefit foreign language learners (Yano et al, 1994), leading to better text comprehension, particularly for people at lower English proficiency levels (Rets and Rogaten, 2021) and children with low reading fluency and weak cognitive skills (Javourey-Drevet et al, 2022).…”
Section: Text Simplificationmentioning
confidence: 99%
“…However, both tasks are rarely studied for question generation (Lyu et al, 2021). Simplification, on the other hand, has demonstrated its values in language learning and reading comprehension (Tweissi, 1998;Inui et al, 2003;Petersen and Ostendorf, 2007;Rets and Rogaten, 2021), and is often treated as a preprocessing step to convert complex sentences into simpler versions before creating questions (Majumder and Saha, 2015;Patra and Saha, 2019). State-of-the-art NLP models for these three tasks are all based on neural generation systems, which are known to suffer from errors and lack of controllability (Maynez et al, 2020).…”
Section: Nlp Tasks For Educationmentioning
confidence: 99%